Hubungan Antara Kemampuan Komunikasi Matematika Dengan Hasil Belajar Siswa MTSS Hubulo - Tya Ayu Palupy; Dewi Belinda (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This correlation study aimed to determine the relationship between students' mathematic communication skills and learning outcomes in mathematic in the research site. The research was conducted in class VII A of MTs Hubulo Islamic Junior High School in Bone Bolango Regency, Gorontalo Province. Simple random sampling was elected as the sampling technique. The instruments consisted of mathematics communication skills and learning outcomes tests. Moreover, the data were collected by giving tests to the research sample. Based on the hypothesis test, it was concluded that there was a positive and significant relationship between mathematics communication skills and student learning outcomes in the research area. The regression equation of Ŷ = 22,314 + 0,347X. This equation showed that per one increase in a student's mathematics communication ability score will be followed by an increase in the mathematics learning result score of 0,347 units at a constant of 22,314. Based on the findings, it is obtained that the correlation coefficient (r) of 0,408 with r Square = 0,166. These results indicated that 16.60% of mathematics communication skills contributed to mathematics learning outcomes, and the remaining 83,40% was influenced by other unexamined variables in this study; this indicated that mathematics communication skills had a weak relationship with student learning outcomes in mathematics lessons.